Mia Couto: a escrita e o outro da língua - Pereira, José Paulo (Navegações, 2014)
O conto “Afinal Carlota Gentina não chegou de voar?”, de Mia Couto, é aqui lido nos seus pressupostos de reflexão crítica, acerca do poder e da lei, do sujeito e da cultura, da diferença e da exclusão, da escrita e da língua. A nossa leitura examina nele as implicações da sobreposição violenta de mundos/culturas divergentes, numa situação de domínio e de alienação colonial. Ali o sujeito híbrido se constitui já como lugar de erosão da identidade colonial, no processo daquela “contramodernidade” de que a História nos dá hoje testemunho, e de que Homi Bhabha nos fala. Mostrar‑se-á enfim que, já no limiar da “pós-modernidade”, a violência do choque entre culturas significa, para o sujeito que a ela se expõe, um profundo dilaceramento ético, provocado pela experiência da heteronomia que atravessa toda a “situação de emergência” colonial. ********************************************************************************** Mia Couto: writing and the other(ness) in language Abstract: The reading of Mia Couto’s short story “Afinal Carlota Gentina não chegou de voar?” [“So, Carlota Gentina has not flown?” / “So, Carlota Gentina has not returned from flight?” are both possible and necessary at the same time, without exclusion] follows the philosophical presuppositions of post-colonial critical thinking regarding power and law, subject and culture, difference and exclusion, as well as writing and language. It examines the implications of a violent overlapping of divergent worlds / cultures in a realm of colonial rule and alienation. There, the hybrid subject establishes himself as a place of colonial identity erosion, in the process of a “counter-modernity” which history has indicated, and which Homi Bhabha tells us about. It will also be shown that, as early as the beginning of the “post-modern” era, the violence of cultural shock signifies for those exposed to it a deep ethical rupture provoked by the heteronomy that crosses the entire colonial state of “emergency”. Keywords: Post-colonial; Short story; Culture; Difference; Identity